Novel highly active and self-healing Co(CO3): XOHy cocatalysts on BiVO4 photoanodes for effective solar water oxidation - Wu, Lijun; Wang, Lei; Zhu, Jie; Sun, Mao; Liu, Xianhu; Schmuki, Patrik; Zhang, Jun (Journal of Materials Chemistry A, 2020)
Recent reports show that Co-Pi cocatalysts on some photoanodes, such as Fe2O3 or BiVO4, accelerate the surface water oxidation rate, acting as a hole extracting layer that improves charge separation or as a "surface passivation agent". In contrast, on semiconductors such as BiVO4, deposition of classic Co-based oxygen evolution catalysts (e.g. Co3O4, CoOOH) leads to a relatively low improvement of the photoelectrochemical (PEC) performance. This illustrates that even though a species may be an excellent electrocatalyst, it may not be an effective co-catalyst for PEC reactions. Clearly, for different semiconductors there is a need to directly identify and prepare specific, highly active and low-cost cocatalysts for promoting PEC water oxidation. Co(CO3)0.5(OH)·0.11H2O (or in general Co(CO3)xOHy) is usually used as a precursor to synthesize a range of Co-based efficient electrocatalysts. Herein, we for the first time show that Co(CO3)xOHy on BiVO4 provides an excellent oxygen evolution reaction activity, even close to the so far most efficient dual-layer FeOOH/NiOOH cocatalysts. Decoration of BiVO4 with Co(CO3)xOHy and the resulting photoanode shows a remarkable enhancement of photocurrent, achieving a photocurrent density of 5.0 mA cm-2 at 1.23 VRHE with an onset potential of 0.3 VRHE, which is one of the highest PEC activities of BiVO4 reported up to now. The outstanding PEC performance can be attributed to the improvement of charge separation and transfer efficiency caused by a uniform thin coating of Co(CO3)xOHy. The Co(CO3)xOHy exhibits the highest density of active sites, the highest surface area, and the best OER activity among the investigated cobalt-based cocatalysts. Remarkably, the Co(CO3)xOHy also displays a self-healing function in borate buffered electrolytes. Therefore, this work not only describes low-cost but highly active cobalt-based catalysts for PEC solar water oxidation, but additionally shows a self-repair function of this system.
CRIS-Team Scopus Importer:2020-02-18